Design of Cartesian Type Manipulator for Automatically Capturing Plant Images Inside Greenhouse - I Dewa Made Subrata; Jacklyn Melania (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Scientific activities often require large amounts of digital image data so it is required a device capable of capturing images automatically. This study aims to design a Cartesian-type manipulator with two translational movement for capturing and storing hydroponic plant images automatically and continuously. The manipulator is programmed to capture and store plant images from 15 different positions for seven consecutive days and two cycles a day, namely at 07.00 AM and 17.00 PM. The 2020 solid work simulation yields a maximum von Mises stress of 13,783 MPa, and a minimum safety factor of 6,869. The manipulator was tested using step period treatments of 0.002, 0.003, 0.004 seconds. The best test results is treatment of 0.002 seconds with an average of x-axis and y-axis positional error was 0.380 cm and 0.076 cm, the average translation speed was 8.96 cm/second. The positioning accuracy on the x-axis and y-axis is 98.9% and 99.8%. The movement stability is quite good around the set point with an error range on the x-axis and y-axis is -0.1 to +0.9 cm and -0.065 to 0.15 cm. System response less than 1 ms and energy consumption of 16,132 watt-hours/cycle. The manipulator is able to work according to the design objectives. Keywords:   Automatic, Continuous, Cartesian manipulator, Digital image, Hydroponic plants